Association between Coagulation Profile and Platelet Lymphocyte Ratio with Karnofsky Performance Status Scale In Brain Tumor Patients - Salsabila, Khansa; Sinurat, Puji Pinta Omas; Nasution, Irina Kemala (Journal of Society Medicine, 2023)
Introduction: Patients with tumor usually show abnormal laboratory coagulation tests, indicating a subclinical hypercoagulable state that contributes to morbidity and mortality. Hematologic markers such as the platelet-lymphocyte ratio (PLR) can be used as an index of tumor progression, high PLR is associated with morbidity and mortality in patients with primary or metastatic tumors. KPS is a method that is widely used to assess the functional status of a patient. The aim of this study is to determine the relationship between coagulation profile and platelet-lymphocyte with Karnofsky Performance Status Scale in Brain Tumor Patients. Method: This study was an observational analytic study with a cross-sectional design using primary data sources taken consecutively from all brain tumor patients who were hospitalized in Inpatient Room at Haji Adam Malik General Hospital Medan who met the inclusion criteria. The parameters analyzed were Prothrombin Time (PT), Activated Partial Thromboplastin Time (aPTT), D dimer (DD), and PLR. Clinical outcome of brain tumor patients was assessed using KPS. To assess the relationship between coagulation marker factors and the ratio of platelets to lymphocytes to KPS, the Spearman and Gamma tests were used. Results: Of the 30 research subjects analyzed, the number of female subjects was comparable to that of males (50%). The highest age is in the age range of 61-70 years by 30%. The highest level of education was high school at 40%, the most research subjects were housewives at 33.3% and the most types of brain tumors were primary brain tumors at 56.7%. The highest KPS score during treatment was found in the <70 group of 76.7%. From the correlation test, it was found that there was a strong, significant relationship between the values of PT (p<0.02 r = -0.731), APTT (p<0.013 r = -0.761), D-dimer (p<0.001 r = -0.737) and PLR (p<0.001 r = 0.78) on the clinical outcome of brain tumor patients assessed by KPS. Conclusion: There is a strong relationship between PT, APTT, D-dimer and PLR values on KPS in patients with brain tumor.